2016
DOI: 10.1371/journal.pone.0168401
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion: -80°C Frozen Blood Products Are Safe and Effective in Military Casualty Care

Abstract: IntroductionThe Netherlands Armed Forces use -80°C frozen red blood cells (RBCs), plasma and platelets combined with regular liquid stored RBCs, for the treatment of (military) casualties in Medical Treatment Facilities abroad. Our objective was to assess and compare the use of -80°C frozen blood products in combination with the different transfusion protocols and their effect on the outcome of trauma casualties.Materials and MethodsHemovigilance and combat casualties data from Afghanistan 2006–2010 for 272 (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 59 publications
3
86
0
Order By: Relevance
“…There has been a resurgence in interest in cryopreservation of platelets over the past decade . Although CPPs have been transfused for prophylactic purposes, the most prevalent indication for CPPs has been the treatment of active bleeding . In the future, CPPs could represent one component in a multiproduct inventory where the choice of product is dictated by individual patient requirements.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a resurgence in interest in cryopreservation of platelets over the past decade . Although CPPs have been transfused for prophylactic purposes, the most prevalent indication for CPPs has been the treatment of active bleeding . In the future, CPPs could represent one component in a multiproduct inventory where the choice of product is dictated by individual patient requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Various options for supplying blood products to distant military settings have been considered, including the use of frozen RBCs and frozen platelets (PLTs). A study by the Netherlands Armed Forces has shown that recovered frozen components are safe and as effective as standard blood components in the treatment of trauma casualties . The option can be successfully applied to the maritime environment; however, it requires a bespoke infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…The early intervention with blood products contributes significantly to correction of coagulopathy and to the control of bleeding . The rapid administration of the whole spectrum of transfusion products is proven to have a positive impact on patient survival; therefore, most current transfusion protocols and hemostatic resuscitation procedures are based on the coadministration of red blood cells (RBCs) and plasma, supplemented with platelet transfusion …”
mentioning
confidence: 99%
“…Use of CPs improves the logistics of maintaining and providing platelet products where and when fresh products are not available. The production of CPs is not technologically demanding, and they can be easily thawed and reconstituted …”
mentioning
confidence: 99%